ANALISIS FRAMING PEMBERITAAN AHOK SEBAGAI CALON GUBERNUR DKI JAKARTA DI HARIAN KOMPAS (Edisi September 2016) - Siswanta, Adi Nugroho Hary Saputro, Maya Sekar Wangi & (Transformasi, 2017)
This research aimed to analyze the news framing Ahok as Jakarta governor candidate inKompas. This study uses qualitative research methods to the analysis of framing. Sources of dataobtained from the text of the news about Ahok as a candidate for Governor of DKI in Kompas editionSeptember 2016. Data were analyzed using analysis of framing a model Pan and Kosicki consisting ofsyntax, script, thematic, and tetoris. The results showed that: (1) Kompas framing at Ahok as a candidatefor governor who is more concerned with the task of serving the people rather than a campaign, by therules leave the campaign, willing to not campaign if compulsory leave revoked, do not take advantage ofits position as a candidate incumbent, and supported by party winning the election; (2) Kompaspreferring the name Basuki than Ahok, this meant that the figure is seen more Ahok Indonesia, moreNjawani while reducing ethnic issues. Kompas wants to show their assimilation efforts undertaken byAhok.Keywords: DKI election, Ahok, Framing Analysis